Texture Analysis using The Neutron Diffraction Method on The Non Standardized Austenitic Steel Process by Machining,Annealing, and Rolling - Priyanto, Tri Hardi; Parikin, Parikin; Li, Meijuan (Makara Journal of Technology, 2016)
Austenitic steel is one type of stainless steel which is widely used in the industry. Many studies on austenitic stainless steel have been performed to determine the physical properties using various types of equipment and methods. In this study, the neutron diffraction method is used to characterize the materials which have been made from minerals extracted from the mines in Indonesia. The materials consist of a granular ferro-scrap, nickel, ferro-chrome, ferro-manganese, and ferro-silicon added with a little titanium. Characterization of the materials was carried out in three processes, namely: machining, annealing, and rolling. Experimental results obtained from the machining process generally produces a texture in the 〈100〉 direction. From the machining to annealing process, the texture index decreases from 3.0164 to 2.434. Texture strength in the machining process (BA2N sample) is 8.13 mrd and it then decreases to 6.99 in the annealing process (A2DO sample). In the annealing process the three-component texture appears, cube-on-edge type texture {110}〈001〉, cube-type texture {001}〈100〉, and brass-type {110}〈112〉. The texture is very strong leading to the direction of orientation {100}〈001〉, while the {011}〈100〉 is weaker than that of the {001}, and texture with orientation {110}〈112〉 is weak. In the annealing process stress release occurred, and this was shown by more randomly pole compared to stress release by the machining process. In the rolling process a brass-type texture{110}〈112〉 with a spread towards the goss-type texture {110}〈001〉 appeared, and the brass component is markedly reinforced compared to the undeformed state (before rolling). Moreover, the presence of an additional {110} component was observed at the center of the (110) pole figure. The pole density of three components increases with the increasing degree of thickness reduction. By increasing degrees of rolling from 81% to 87%, the value of orientation distribution function increases by a factor about three times.